Europium Doped TiO2−Ta2O5 Heterostructure for Photodegradation of Dyes. Issue 10 (11th March 2020) - Ghugal, Sachin G.; Vidyasagar, Devthade; Ghugal, Sandip G.; Shende, Ashok G.; Toshali Bhoyar, Ms.; Umare, Suresh S.
Abstract: A europium doped TiO2 −Ta2 O5 mixed oxide heterostructure prepared by wet impregnation method shows improved visible light absorption than the anatase TiO2 and undoped TiO2 −Ta2 O5 heterostructure. The structural analysis suggested the presence of mixed TiO2 and the orthorhombic Ta2 O5 phase. The photoactivity of Eu‐doped TiO2 −Ta2 O5 composites assessed towards the degradation of a model indigo carmine (IC) dye revealed high photodegradation activity than the individual metal oxides. The combination of efficient photo‐excitons separation and enhanced visible‐light absorption are corroborated factors responsible for the upgraded photocatalytic activity. Importantly, the prepared heterostructure found to be photostable and active for six repetitive recycles. Abstract : A europium doping of TiO2 tuned its optoelectronic properties. Furthermore, Eu‐doped TiO2 −Ta2 O5 hybrid composite shows extended visible light absorption. The photophysical and photocatalytic behavior of europium doped TiO2 /Ta2 O5 heterostructure was explored for degradation of indigo carmine (IC) dye, which shows almost seven‐times enhanced photodegration activity than counter single component metal oxides.